"O despertar": uma história das práticas da educação rural em Caxias do Sul (1947-1954) - Dewes, Elisângela Cândido da Silva (My University, 2019)
This study examines the models and practices disseminated to the community of the rural school of Caxias do Sul, from the understanding surrounding the contents in the journal Despertar - object and source of this research, produced by the Public Instruction Board of this city, from 1947 to 1954. The objective was to analyze the feelings triggered in the rural community through the reading Desperetar, on the models and practices disclosed by the teaching body. The study also identifies how the use of Despertar, through texts, images and diagramming, influenced the construction of a group identity; historically contextualizes the period in which the journal was produced, examining its influences; and seeks understanding on how the formation of teachers for that rural area was related to the educational policies of the time. The study is in the field of the History of Education and has, as theoretical reference, the Cultural History. The research method used was documental analysis, and the methodological procedure was the categorization of texts, iconography and graphic components present in the fifty-three issues of the Despertar journal. The analyzed documents also include aspects of education legislation, the transcript of an interview given to local researchers by Professor Ester Troian Benvenutti - creator of Despertar, and other documents by the Municipal Public Education Board. The considerations about the journal are that it cooperated to strengthen the identity of the inhabitants of the rural area by disseminating content aligned with the needs of these people, and that its contents exhibit the influence of both pedagogical ruralism and nationalism, on the education promoted in the rural area. It is still possible to note that the journal was somewhat of a guide, with orientations for different practices aimed at rural communities, and that it was a pedagogical aid for the local teachers, ensuring that their work was adequate to the daily life particularities of rural people and aligned with the public administration's aspirations for education in this context. [resumo fornecido pelo autor]
Este estudo investiga os modelos e práticas disseminados para a comunidade da escola rural de Caxias do Sul, a partir da compreensão acerca das representações contidas no periódico Despertar – objeto e fonte desta pesquisa, produzido pela Diretoria de Instrução Pública deste município, no período de 1947 a 1954. O objetivo foi o de analisar os sentidos criados pela comunidade da área rural, possibilitados pela leitura do Despertar, sobre os modelos e práticas divulgados pelo órgão de ensino. O estudo ainda identifica como a utilização do periódico Despertar, por meio dos textos, imagens e diagramação, influenciou a construção de uma identidade de grupo; contextualiza historicamente o período em que o periódico foi produzido, averiguando as influências; e busca a compreensão sobre como a formação de professores, para a atuação no contexto rural, relacionava-se com as políticas educacionais da época. O estudo encontra-se no campo da História da Educação e tem, como referencial teórico, a História Cultural. Como método de pesquisa foi utilizada a análise documental, e como procedimento metodológico, a categorização de textos, iconografia e componentes gráficos, compreendidos nas cinquenta e três edições do Despertar. Compõem ainda os documentos analisados: aspectos da legislação sobre o ensino; a transcrição de uma entrevista concedida, a pesquisadores locais, pela professora Ester Troian Benvenutti – idealizadora do Despertar; além de outros documentos da Diretoria de Instrução Pública Municipal. Entre as considerações acerca de tal periódico, a de que cooperou para o fortalecimento da identidade dos habitantes da área rural, enquanto divulgava um conteúdo alinhado às necessidades dessas pessoas; também, a de que suas matérias evidenciam a influência tanto do ruralismo pedagógico, quanto do nacionalismo, sobre a educação promovida na área rural. Ainda é possível compreender que o periódico constituiu-se em uma espécie de guia com orientações para diferentes práticas, voltadas às comunidades da área rural; e, que foi um suporte pedagógico para os professores, colaborando para que a atuação do professor junto a essas comunidades, estivesse adequada as particularidades do cotidiano da vida das pessoas da área rural, e alinhada aos anseios da administração pública quanto a educação nesse contexto. [resumo fornecido pelo autor]
Keywords: Educação rural - Caxias do Sul (RS); Prática de ensino; Educação - História; Ensino - Periódicos; Rural Education - Caxias do Sul (Brazil); Teaching Practice; Education - History; Teaching - Periodicals